Determinan Profitabilitas Bank Konvensional yang Terdaftar di Otoritas Jasa Keuangan Indonesia - Meily Juliani; Rachel Tanwijaya (Faculty of Economics, Universitas Internasional Batam, 2022)
Purpose - This paper aims to find out what factors will affect the Indonesia conventional banks’ profitability. The concern of doing this paper is based on the report shown by the Banco Bilbao Vizcaya Argentaria’s reports which showed an instability of financial ratio in Indonesia. Research Method - The paper uses the secondary method in collecting information that is used in the paper. The sample for the panel data consists of 95 conventional banks in Indonesia that are listed in the Financial Service Authority of Indonesia (OJK) for the year 2017-2021. The fixed effect model is used for the paper. Findings – Indonesia conventional banks’ profitability are highly impacted by the non-performing loans (measured by non-performing loans over gross loans), operational cost to operational income ratio, bank size, and deposit ratio. These impacts show a negative relationship between the ratios and bank’s profitability. As these ratios increase, the bank’s profit decreases. However, these relationships do not reflect the same way on capital adequacy ratio, loan to deposit ratio, and diversification. These three ratios show an insignificant impact on bank’s profitability. Implication - The paper has shown the impact of each variable to the bank profitability. Keeping bank’s profitability stable is a must for all bank’s top managements responsibility. The findings of the paper could help banks’ top managements to find strategies for the bank to increase those variables which impact positively to the bank profitability and reduces the activities which will cause the banks’ losses.